A comprehensive grammar of the english language - Quirk, Randolph; Greenbaum, Sidney; Leech, Geoffrey; Svartvik, Jan. ([S.l.] : Longman, 1985)
An indispensable store of information on the English language, written by some of the best-known grammarians in the world.